2010
DOI: 10.4103/0972-0707.62631
|View full text |Cite
|
Sign up to set email alerts
|

Fluorosis varied treatment options

Abstract: Fluorosis has been reported way back in 1901. The treatment options for fluorosis are varied depending upon individual cases. This article comes from Madurai in India where its surrounding towns are fluorosis-prone zones. The purpose of this article is to report various treatment options available for dental fluorosis; this is the first time that complete full mouth rehabilitation for dental fluorosis is being reported. This article also dwells on the need for the dentists to be aware of their local indigenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 18 publications
0
40
0
1
Order By: Relevance
“…Limeback et al reported an esthetic improvement of DF lesions through physical enamel abrasion with a diamond bur. This mechanical removal of pigmented enamel has been described in the literature . The advantage of this technique is in its celerity in reaching the desired esthetic in cases of mild or moderate DF.…”
Section: Discussionmentioning
confidence: 99%
“…Limeback et al reported an esthetic improvement of DF lesions through physical enamel abrasion with a diamond bur. This mechanical removal of pigmented enamel has been described in the literature . The advantage of this technique is in its celerity in reaching the desired esthetic in cases of mild or moderate DF.…”
Section: Discussionmentioning
confidence: 99%
“…From score 4 to 9, more invasive treatments are necessary. Options range from resin-based composite restorations, faceting of affected teeth or even total crowns (39). In each of the treatment options described above, each one has its own advantages and disadvantages; a good clinician should be aware of all the treatment options available assess its merits and demerits and select the best treatment option according to individual patient needs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned options, full-coverage restorations are another choice for moderate-to-severe discolouration and surface pitting 13. Full coverage restoration requires very careful planning as well as execution of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found few case reports that described the management of generalised severe fluorosis 13 17. The present case is an example of stepwise full-mouth rehabilitation utilising different restorative approaches to get an aesthetically, as well as functionally, acceptable outcome.…”
Section: Discussionmentioning
confidence: 99%